Does Westminster (Still) Represent the Westminster Model? An Analysis of the Changing Nature of the Uk's Political System. Issue 2 (December 2015) - Strohmeier, Gerd
In the first edition of his Patterns of Democracy (1999 ), Lijphart used the term 'Westminster model' 'interchangeably with majoritarian model. Despite both the constitutional reforms introduced since the change of government in 1997 and the outcome and consequences of the 2010 general election, Lijphart concluded in the second edition of his book (2012a ) that 'recent changes in British politics do not change the overall character of Britain as a prime example of majoritarian democracy.' Lijphart's perspective is challenged by this article–-which also examines the effect of the 2015 general election on the nature of the Westminster system through the prism of Lijphart's Patterns of Democracy. It is argued that first, the Westminster system has never represented the majoritarian ideal; second, that it has noticeably moved towards greater consensus as a result of the various constitutional reforms introduced since the change of government in 1997 on the one hand and the outcome and consequences of the 2010 general election on the other; and third, that the 2015 general election has somehow stopped this general trend towards greater consensus.